2020
DOI: 10.1002/slct.202002101
|View full text |Cite
|
Sign up to set email alerts
|

The Nonapeptide RWQWRWQWR: A Promising Molecule for Breast Cancer Therapy

Abstract: The palindromic nonapeptide H‐1RWQWRWQWR9‐NH2 (LfcinB (21–25)Pal) was synthetize and scaled following the good manufacturing practices (GMP) guidelines to obtained batches up to 1 g of pure peptide which evidencing their synthetic viability. Its cytotoxic effect was tested against breast cancer cell lines MDA‐MB‐231 and MCF‐7 and was dependent on concentration against both. The IC50 values were 135 μM and 66 μM, respectively. Against MCF‐7 the peptide exerts its greater cytotoxic effect at 135 μM, diminishing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Also, the addition of Trp or another hydrophobic amino acid to this cationic sequence has improved the effect because of its ability to disrupt the cell membrane and reach intracellular targets . Both approaches have been tested in the palindromic peptide R-1-R, whose configuration of alternation of basic and hydrophobic residues induces an advantageous effect over the lactoferricin minimal motif, inducing cytotoxicity against breast MCF-7, MDA-MB-231, MDA-MB-468, and colorectal CaCo-2 cancerous cell lines while exhibiting no or significantly less activity on HEK-293, MCF-12, CEMB, and primary culture fibroblasts. ,, Also, a replacement of Arg to Lys residues has been made in this palindromic sequence; this approach does not improve its antibacterial activity or its cytotoxic effect.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Also, the addition of Trp or another hydrophobic amino acid to this cationic sequence has improved the effect because of its ability to disrupt the cell membrane and reach intracellular targets . Both approaches have been tested in the palindromic peptide R-1-R, whose configuration of alternation of basic and hydrophobic residues induces an advantageous effect over the lactoferricin minimal motif, inducing cytotoxicity against breast MCF-7, MDA-MB-231, MDA-MB-468, and colorectal CaCo-2 cancerous cell lines while exhibiting no or significantly less activity on HEK-293, MCF-12, CEMB, and primary culture fibroblasts. ,, Also, a replacement of Arg to Lys residues has been made in this palindromic sequence; this approach does not improve its antibacterial activity or its cytotoxic effect.…”
Section: Discussionmentioning
confidence: 99%
“…22 Both approaches have been tested in the palindromic peptide R-1-R, whose configuration of alternation of basic and hydrophobic residues induces an advantageous effect over the lactoferricin minimal motif, inducing cytotoxicity against breast MCF-7, MDA-MB-231, MDA-MB-468, and colorectal CaCo-2 cancerous cell lines while exhibiting no or significantly less activity on HEK-293, MCF-12, CEMB, and primary culture fibroblasts. 6,15,23 Also, a replacement of Arg to Lys residues has been made in this palindromic sequence; this approach does not improve its antibacterial activity 24 or its cytotoxic effect. Modifications of the length of active peptides have been shown to result in a major improvement of their antimicrobial activity.…”
Section: ■ Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have demonstrated that the combination of drugs offers numerous advantages over monotherapy, which include reduced dosage, synergistic re- Similarly, Barragán-Cárdenas et al have reported that this palindromic peptide exhibits a rapid cytotoxic effect on breast cancer cells. They also tested its selectivity on primary fibroblasts, non-cancerous MCF-12 cells, and BMEC bovine mammary cells, with minimal effect on them [47,48].…”
Section: Microscopymentioning
confidence: 99%